MOTION GRAPHICS: AN ENTERTAINING AND ACCESSIBLE LEARNING MEDIA FOR THE STUDENTS - Perdani, Yella Dezas (Bina Nusantara University, 2024)
In the Covid-19 pandemic, teachers and students must continue learning at home online. Online learning requires teachers to be more selective and creative in preparing teaching materials, including learning media. Learning media must be informative, contain all the material to be taught, and be interesting so students are interested in learning. One of the informative and interesting learning media that is currently widely used is video. Teachers must prepare videos that suit the material and students' abilities. Technology has been and is still being used on a large scale by teachers to assist teaching in the classroom. Both applications and products from these applications support the teaching and learning process and help students understand learning. One technological product currently widely used is video-based learning, and one type of VBL that can be used to create interesting learning media is Motion Graphic learning. MG is the process of designing, writing and moving images whose final product can be learning media. This Community Service Activity (PKM) is designed to educate teachers on the use of Motion Graphics as a learning medium for students. As a result, it is expected that this training will benefit teachers.